PROFIL DAN PROSPEK BISNIS MINYAK DARA (Virgin Coconut Oil/VCO) DI KABUPATEN CILACAP - Anny Hartati; Altri Mulyani (Universitas Tadulako, 2009)
Cilacap regency is an area significantly potential for virgin coconut oil (VCO) business development. Mostly consisted of coastal areas where coconut trees are abundant, it can support the development of VCO business as the needed raw materials can be met easily. The research aims were to identify the profile business of VCO in Cilacap regency and the level of profit the business making from VCO, to determine the amount of inputs used in the business and the efficiency of the inputs, to determine the efficiency of making VCO business, to determine the added value gain from VCO business, to determine labors absoRp.tion from VCO business and to identify the potential VCO business in the future based on the business strengths, opportunities, weaknesses and challenges. The research material included were the VCO business data, production factors, products number, production costs, product price, productivity, and profitability. A survey method was used in which samples were puRp.osively taken. The targets were 25 VCO households industry in Cilacap regency which are partners of Department of Forestry and Plantation of Cilacap Regency. Data analysis used were descriptive analysis, the analysis of costs and revenue, the analysis of R/C ratio, the analysis of B/C ratio, the analysis of Return on Investment (ROI), the analysis of Break Even Point (BEP), and the value added analysis. The mean benefit cost ratio (B/C ratio) and VCO ROI on agroindustry were 0.318 and 31.77%, respectively, indicating that the VCO agro industry in this research area has the ability to create benefit. The added value of the agroindustry was IDR 1,376 per unit generated from the labor component (12.86%), the input (49.52%), and the profits (37.62%). The labor absoRp.tion during production process was varied from 75 HKSP to 320 HKSP, with an average of 129,20 HKSP. The strategies of VCO agro industry development in the future need to consider the potential strengths, opportunities, weaknesses and challenges the business encounters as found in the research. The prospective of VCO business development in Cilacap is thus very promising.